The Development of Consumer Protection Law on Digital Content - Treesomphong, Sakunphong; Nuchprayool, Bajrawan (Rajapark Journal, 2021)
The purposes of this study were as follows: (1) to study the digital content and the Consumer Protection on digital content; (2) to compare the foreign Consumer Protection laws to the Thai Consumer Protection laws; (3) to analyze the direction of developing the consumer protection laws on digital content; and (4) to suggest the development of Consumer Protection laws on digital content. This study was a documentary research, study of the Consumer Protection laws on digital content, including enforcing Thai laws, international laws, and foreign law in comparative law perspective. The research is involved in the definition and the scope of Consumer Protection of digital content, Consumer Protection for pre-contract and post-contract for the contract to supply digital content, the standard for digital content and consumer remedial threshold in case of supplying digital content that non-conformation of said standard, consumer protection in case of entrepreneur does not have the right to supply digital content and digital content cause damages to other digital content or damages of consumer’s devices issue, right to freely terminate the contract to supply digital content and unfair contract issues of consumers. The result of the research illustrated that the current Thai Consumer Protection law in many versions is inappropriate because they have not been specifically constructed applicable to digital content’s consumers which may cause injustice to the consumers. Accordingly, this article was to present the development of Consumer Protection laws on digital content by applying international laws, namely EU law, and foreign laws, including UK law and German law as a guideline for the development of the Consumer Protection laws on digital content to be enforced in Thailand. The authors suggest that it is necessary to legislate a specific individual law for consumer protection on digital content.